Multi-Objective Control Method in Structural Stress Interval Reliability Based on Epsilon Algorithm - Sun, Zuo Zhen; Ma, Kai; Meng, Guang Wei; Li, Feng (Applied Mechanics and Materials, 2013)
A kind of structural stress reliability control method was presented. In this article, the interval extension of multi-objective control algorithm was applied to control the structural stress reliability. By the control of the structural interval parameters, this method has realized the goal of controlling the multiple static interval reliability indexes. To insure the accuracy of the structural reanalysis, the Epsilon algorithm was used in the process of the structural reanalysis when a wide range of modification happened in the interval parameters. This method can both get a satisfactory accuracy, and improve the speed of the reanalysis. The results of the example further proved that the proposed method can be effectively applied in the multi-objective control of the structural stress interval reliability.